Investigation of ecological potentials of the Eger Model Region by GIS methods - Őrsi, Anna; Kertész, Ádám (Hungarian Geographical Bulletin, 2014)
Various parts of a landscape unit or region can be used for multiple purposes. Before the collectivisation of agricultural fields in the 1960s, the use of the land was more or less in accordance with the given natural conditions. Aft er collectivisation, huge plots were created, neglecting the features of the capability of the area. The map of ecological potential types shows favourable and unfavourable conditions for agricultural and forestry use, i.e. it indicates which parts of the region off er the best ecological conditions for arable cultivation, viticulture, fruit production, cultivation of meadows and pasture, just to mention a few. A capability assessment using GIS is being carried out for the total area of the Eger region. The database used for the capability analysis contains the Corine 1990 and 2006 data, soil maps and the National Gully Cadastre. The map is compared with present-day land use and the discrepancies between landscape capability and present land use are identified. Suggestions are made to optimise land use according to the capability map. Alterations since the change of the regime in 1989 have been determined and analysed from the aspect of suitability, as well.